2002
DOI: 10.1071/sr02026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agricultural management on Vertosols in Tasmania

Abstract: Attributes of 21 Vertosols in 2 different regions of Tasmania were assessed using field and laboratory techniques to determine differences associated with 3 local forms of agricultural management (long-term pasture, rain-fed cropping and irrigated cropping). Vertosols in the northern Midlands had better physical properties (lesser bulk density and penetration resistance, and greater porosities and water holding capacities), poorer nutrient status (lower pH, exchangeable bases, and extractable P) and better bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…However, BD in this treatment was still within the optimum range (0·9–1·2 Mg m −3 ) for fine‐textured soils (Reynolds et al, ). Similar differences in BD owing to differences in SOC have been observed for loamy soil by Reynolds et al () and for clay soil by Cotching et al (). Although Reynolds et al (, ) and Drewry (Drewry, ) suggested the 0·9 to 1·2 Mg m −3 range as optimal for crop production on fine‐textured soils, the upper limit in fine‐textured soil is 1·25–1·30 Mg m −3 (McQueen & Shepherd, ), whereas root elongation becomes severely restricted in fine‐textured soil at BD values of 1·4–1·6 Mg m −3 (Jones et al, ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, BD in this treatment was still within the optimum range (0·9–1·2 Mg m −3 ) for fine‐textured soils (Reynolds et al, ). Similar differences in BD owing to differences in SOC have been observed for loamy soil by Reynolds et al () and for clay soil by Cotching et al (). Although Reynolds et al (, ) and Drewry (Drewry, ) suggested the 0·9 to 1·2 Mg m −3 range as optimal for crop production on fine‐textured soils, the upper limit in fine‐textured soil is 1·25–1·30 Mg m −3 (McQueen & Shepherd, ), whereas root elongation becomes severely restricted in fine‐textured soil at BD values of 1·4–1·6 Mg m −3 (Jones et al, ).…”
Section: Discussionsupporting
confidence: 84%
“…Overall, the soil strength values were very high, which might partly be explained by the high clay content but mainly by soil compaction. In the study of Cotching et al () on Vertisols with high clay content, the penetration resistance increased to a mean value of 3·2 MPa at a depth of 60 cm. In our study location in the Mekong Delta, clay content was even higher compared with that of the study of Cotching et al (), resulting in an even higher penetration resistance (between 3 and 4 MPa at a depth of 60 cm).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In southern Kenya, studies on stocking rates showed that lighter density stocking (4 heifers ha -1 ) maintained the highest output per head while heavy stocking density (16 heifers ha -1 ) resulted in the highest soil loss, lowest infiltration rate and highest bulk density (Mworia et al, 1996). In Tasmania, Australia, studies of long-term management systems indicated that pasture paddocks developed stronger soil structures and smaller aggregates than cropped paddocks, which had larger clods (Cotching et al, 2002). Where livestock and arable crops co-exist, there is need to balance livestock numbers, pasture and cropped lands in order to maintain and/or enhance the soil physical properties (Mworia et al, 1996;Taddese et al, 2002).…”
Section: (C) Cropping Systemsmentioning
confidence: 97%
“…The mean values of HC of soils were 0.83, 0.85, 0.90, and 0.86 cm hr -1 for RW, RC, RL, and RF cropping systems, respectively (Table 2). Rice-legume cropping system notable for organic carbon build-up in soils, which improves soils aggregation (Cotching et al, 2002), reduces pH and ESP and enhance the hydraulic conductivity of the soils (Bhattacharyya et al, 2000). The mean values of MWD of soils were 0.70, 0.86, 0.79, and 0.71 mm for RW, RC, RL, and RF, respectively (Table 2).…”
Section: Soil Physical Propertiesmentioning
confidence: 99%